Supervision, Interprofessional Collaboration, and Patient Safety in Intensive Care Units during the COVID-19 Pandemic - Patterson, Aileen; Hennessy, Martina (American Thoracic Society, 2021)
Background: To meet coronavirus disease (COVID-19) demands in the spring of 2020, many intensive care (IC) units (ICUs) required help of redeployed personnel working outside their regular scope of practice, causing an expansion and change of staffing ratios. Objective: How did this composite alternative ICU workforce experience supervision, interprofessional collaboration, and quality and safety of care under the unprecedented clinical circumstances at the height of the first pandemic wave as lived experiences uniquely captured during the first peak of the pandemic? Methods: An international, cross-sectional survey was conducted among physicians, nurses, and allied personnel deployed or redeployed to ICUs in Utrecht, New York, and Dublin from April to May of 2020. Data were analyzed separately for the three sites. Quantitative data were treated for descriptive statistics; qualitative data were analyzed thematically and combined for general interpretations. Results: On the basis of 234, 83, and 34 responses (response rates of 68%, 48%, and 41% in Utrecht, New York, and Dublin, respectively), we found that the amount of supervision and the quality and safety of care were perceived as being lower than usual but still acceptable. The working atmosphere was overwhelmingly felt to be collaborative and supportive. Where IC-certified nurse-to-patient ratios had decreased most (Utrecht), nurses voiced criticism about supervision and quality of care. Continuity within the work environment, team composition, and informal ("curbside") consultations were critical mediators of success. Conclusion: In the exceptional circumstances encountered during the COVID-19 pandemic, many ICUs were managed by a composite workforce of IC-certified and redeployed personnel. Although supervision is critical for safe care, supervisory roles were not clearly related to the amount of prior ICU experience. Vital for satisfaction with the quality of care was the span of control for those who assumed supervisory roles (i.e., the ratio of certified to noncertified personnel). Stable teams that matched less experienced personnel with more experienced personnel; a strong, interprofessional, collaborative atmosphere; a robust culture of informal consultation; and judicious, more flexible use of rules and regulations proved to be essential.
PUBLISHED
Keywords: COVID-19; Intensive care; Interprofessional collaboration; Quality and safety of care; Supervision